JMJD3-mediated HADH demethylation orchestrates hepatocyte maturation through fatty acid β-oxidation-dependent histone acetylation - Haibin Wu; Sen Chen; Huanhuan Shan; Wenjiao Yan; Changlu Qin; Shoupei Liu; Xiangting Cao; Jinzhi Du; Yongjian Zhou; Yuyou Duan (Experimental & Molecular Medicine, 2026)
Abstract Functionally mature hepatocyte generation requires coordinated genetic, metabolic, and epigenetic regulation. Although transcriptional regulation governing hepatocyte differentiation has been extensively studied, how metabolic remodeling interacts with epigenetic regulation during hepatocyte maturation remains poorly understood. Using a human embryonic stem cell-derived hepatocyte organoid differentiation model, we identified JMJD3 as a critical regulator of hepatocyte maturation through metabolic–epigenetic coupling. Mechanistically, JMJD3 activated the fatty acid β-oxidation (FAO) enzyme HADH by removing repressive H3K27me3 marks at its locus, thereby promoting FAO activity during hepatocyte maturation. Enhanced FAO increased acetyl-CoA production, which subsequently promoted EP300-mediated H3K27ac deposition at hepatocyte maturation-associated genes. Functional inhibition of JMJD3, HADH, or FAO impaired hepatocyte maturation, resulting in lipid droplet accumulation and reduced expression of hepatocyte maturation markers. Conversely, restoration of acetyl-CoA partially rescued these maturation defects, supporting a functional link between FAO-dependent metabolism and histone acetylation. Collectively, our findings establish a JMJD3–HADH–FAO–acetyl–CoA regulatory axis that coordinates metabolic remodeling and epigenetic regulation during hepatocyte maturation.